Entwicklung eines Simulationsprogrammes zur Evaluation und Optimierung der OP-Personaleinsatzplanung in einem deutschen Krankenhaus - Adrian Schmutzler (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2015)
– The surgical unit typically is the biggest cost and revenue center in full-service hospitals, but also a facility with outstanding complexity. This has led to particular interest in the topic at the executive offices and in academic research. While most publications deal with the scheduling and stringing together of operating theaters, this work investigates the planning process in advance of those actions. The thesis presents a multiagent simulation tool, which describes surgical workforce planning based on a model process from a particular German hospital. It combines both key performance indicators and staff satisfaction to study the effect of parameter changes as comprehensively as possible. For evaluation of the program and to draw first conclusions on the planning process a general analysis of influence factors is performed, supplemented by a case study based on a particular model scenario. The simulations yield that effective and satisfying compensation for sickness induced staff shortages is only available by increasing the available workforce in the first place, while other influence factors do not exhibit solely positive impact. As payment for required additional staff exceeds accessible savings in planning cost by one order of magnitude, though, the applicability of direct results is limited. The simulation tool itself however represents a powerful planning environment for hospital managers, so they can tune parameters with their particular priorities in mind.
urn:nbn:de:bvb:703-epub-2050-0
Keywords: 650; OP-Personaleinsatzplanung; Krankenhaus; Simulation; Simulationsprogramm